Immediate Implant Placement into Extraction Sockets with Labial Plate Dehiscence Defects: A Clinical Case Series. (27th April 2015) - Sarnachiaro, Guido O.; Chu, Stephen J.; Sarnachiaro, Evangelina; Gotta, Sergio Luis; Tarnow, Dennis P.
Abstract: Purpose: To measure the buccal plate reconstruction of extraction sockets with labial plate dehiscence defects using a bone allograft in combination with an absorbable collagen membrane and a custom‐healing abutment at the time of tooth removal. Materials and Methods: Ten patients underwent immediate implant placement and reconstruction of the buccal plate. Cone beam computed tomography (CBCT) was performed preextraction, immediately after bone grafting and implant placement (day 0), and between 6 and 9 months following implant surgery. Measurements were taken at three levels: coronal (L1), middle (L2), and apical (L3) level. Results: Implants placed into sockets with labial plate dehiscence defects demonstrated radiographic reformation of the labial plate dehiscence defect at 6 to 9 months posttreatment. The net gain in labial plate on cone beam computerized tomography (CBCT) in L1 and L2 was 3.0 mm, where 0 mm existed at pretreatment. The minimum amount of labial plate thickness of 2.0 mm was achieved in all treated sites, evaluated radiographically at 6 to 9 months postoperatively, in a single procedure, without flap elevation and maintaining the gingival architecture and satisfactory esthetics. Conclusion: Placing an absorbable membrane, bone graft, and custom‐healing abutment at the time of flapless anterior tooth extraction and immediate implant placement into a socket with a labial osseous dehiscence is a viable clinical technique to reconstitute the absence of the labial bone plate.